PENGARUH MOTIF PENGGUNAAN ZOOM MEETING PADA PELAKSANAAN KELAS BESAR TERHADAP EFEK PESAN DAN KEPUASAN MAHASISWA (Survei Pada Mahasiswa UPN Veteran Jakarta) - Siti Masnah Marliana, (2022)
The purpose of this study was to examine the effect of using the Zoom Meeting platform as an online learning media channel used by UPN Veteran Jakarta students in large class lectures on messages effects and student satisfaction by using the uses and gratifications theory. This study used an associative quantitative approach with a survey method by distributing questionnaire in the form of Google Forms to 385 active students of UPN Veteran Jakarta who attend large class lectures in each of the subjects. The sampling technique used is the Stratified Proportionate Random Sampling technique, using the Taro Yamane formula and an error value of 5%. This study has 3 research variables involve 1 independent variable and 2 dependent variables, so simply tested twice. Based on the Determination test, the usage of zoom meetings contributed 69.5% of the message effect and contributed 57.6% of student satisfaction. The results of the Gap Analysis show that the Mean GS is smaller than the Mean GO, so it can be said that motive of the usage zoom meeting media for large class lectures satisfies the students. If it is associated with the Uses and Gratifications theory, this study shows that same as the assumptions of the theory, which the audience uses the media to fulfill their needs and get satisfaction. This can be seen in the satisfaction of students with the usage of zoom meetings which they use as learning media in large class lectures.